Pengaruh Corporate Governance terhadap Firm Value dengan Market Competition sebagai Variabel Intervening - Magdalena Jullina Lier, Maria; Purwohedi, Unggul; Muhammad Zairin, Gentiga (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
This study is a quantitative research that examines the influence of corporate governance on firm value, with market competition as an intervening variable. The sample in this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022, totaling 128 companies with a total of 384 data samples. Hypothesis testing was conducted using multiple linear regression analysis by software SPSS 25. The results of this study indicate that: (1) Corporate Governance has a positive influence on the Firm Value of manufacturing companies in Indonesia, (2) Market Competition has a positive influence on the Firm Value of manufacturing companies in Indonesia, (3) Corporate Governance mediated by Market Competition has a positive influence on the Firm Value of manufacturing companies in Indonesia.